Tensile and thermal properties of oil palm empty fruit bunch regenerated cellulose biocomposite films using ionic liquid - Nur Liyana Izyan, Zailuddin
The regenerated cellulose (RC) biocomposite films from oil palm empty fruit bunch (OPEFB) and microcrystalline cellulose (MCC) were prepared using ionic liquid. N, N Dimethylacetamide (DMAc) and Lithium Chloride (LiCl) were used as solvent system to dissolve the regenerated cellulose, at room temperature. The partially dissolve of RC and subsequently convert onto matrix domain embedding the reinforcement of the nondissolve RC. In this study, the OPEFB contents were varied from 1, 2, 3 and 4 wt% and MCC were fixed at 3 wt%. The effect of OPEFB contents and chemical modification using Butylmethacrylate acid (BMA) and Methacrylic acid (MAA) on X-Ray diffraction, tensile properties, morphology study, thermal properties and FTIR of RC biocomposite films were investigated. It was found that at 2 wt% of OPEFB contents showed the highest crystallinity index (CrI), tensile strength and modulus of elasticity of RC biocomposite films, but lower elongation at break than other OPEFB contents. The temperature at maximum rate of weight loss (Tdmax) and weight loss at temperature 300 °C (T300) decreased with increasing OPEFB contents, while weight loss at temperature 600 °C (T600) increased. The morphology study of OPEFB RC biocomposite films exhibited at 2 wt% contents of OPEFB has better dispersion of RC into the matrix. The chemical modification of OPEFB using BMA or MAA indicated enhance the properties of treated RC biocomposite films. The Tdmax of treated RC biocomposite films with BMA or MAA were higher than the untreated RC biocomposite films. At temperature T300 and T600 degradation showed that treated RC biocomposite films with BMA or MAA have lower weight loss. This indicated that treated biocomposite films had better thermal stability. The enhanced of interfacial interaction and dispersion of treated RC biocomposite films with BMA or MAA were proven by SEM study. The FTIR spectra of treated RC biocomposite films indicated the formation of esterification reaction between cellulose from OPEFB and MCC with BMA or MAA. The treated RC biocomposite films with BMA have higher crystallinity index, tensile strength, modulus of elasticity and thermal stability compared to treated RC biocomposite films with MAA.